A educação na Guiné-Bissau: perspectivas na atualidade o ensino básico em questão - Sané, Samba (2019)
The present study, whose theme is Education in Guinea-Bissau: Current Perspectives, with emphasis on the role of basic education, aimed to highlight the role and purpose of education for the socio-cultural and economic development of independent Guinea-Bissau, taking into account the overcoming of its colonial past and facing current challenges. This is because the Partido Africano da Independência da Guiné e Cabo Verde, during the struggle for national liberation for the independence of the country, printed a new type of education in schools created in the liberated regions, based on an idea of freedom and dignity of the human person, in solidary progress and social justice, in a few words, a Liberating Education, and which evidently intended to extend it to schools throughout the country after independence, an education contrary to that imposed on the local populations by the Portuguese colonialists, during centuries of domination and exploitation. Having as a research question: what educational alternatives for basic education are possible to overcome the influences of colonial education today that respond to the aspirations of a country that seeks to affirm its identity? The objective is, therefore, to explain the relationship between the overall development project of the society and its basic education project. For the development of this research, the Case Study method was used, which is identified as a qualitative research, and data collection was carried out through theoretical research, using works and documents about the the reality of the country, as well as through Analysis of the data was performed. From this it is concluded that, despite 45 years of independent country, up to the present moment, Basic Education has not been achieved that reaches the entire population, neither in terms of quantity nor quality. This is because, due to the lack of qualified and sufficient human resources to identify the main problems and challenges of education and to define strategies for action, the lack of infrastructure and financial resources meant that all of the country development initiatives, projects and programs were almost entirely dependent on foreign aid, including to operate the public machinery itself. Moreover, permanent political instability has been and continues to be a major obstacle to the functioning of the Republic powers, and the construction of an educational system and basic education that responds to the social and development needs of the country. Therefore, in order to overcome the influence of colonial education and to build an education system and basic education that responds to the aspirations of affirming the country identity, Guinea-Bissau must build a permanent Social Peace and Good Governance , since these are indispensable for internal and external trust to be re-established, and it is also the basis or starting point for establishing the virtuous circle that it needs. It is not only a matter of permanently establishing authentically republican institutions, but also of equipping the Administration with the capacity to conduct the profound transformations designed during the struggle and after independence, which have not yet materialized.